Teenage boys and girls at a graduation party - Unknown:::Creator::::::::::::
Photograph shows a large group of well-dressed teenage boys and girls at a party. Many of them look like they have been dancing. There is a large sign on the back wall that reads: "In honor of graduates" and there are streamers and balloons decorating the ceiling.